Spectrum of Etiologies and Clinical Presentation of Patients with Extraocular Motility Disorders Presenting to a Neuro-Ophthalmology Clinic - Ijaz, Umar; Khan, Taimoor Ashraf; Khan, Muhammad Imran Sarwar; Abbas, Hussnain; Hameed, Asem; Rauf, Abdul (Pakistan Armed Forces Medical Journal, 2023)
Objective: To provide an account on the demographics, etiology, co-morbidities, presentation findings and frequency of patients with cranial nerve palsies presenting to our Neuro-Ophthalmology clinic. Study Design: Cross-sectional study. Place and Duration of Study: Department of Neuro-Ophthalmology, Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi, Pakistan from Dec 2017 to Jun 2022. Methodology: A total of 82 patients were included in the study. The data was compiled on a single proforma by a single investigator which included Co-morbidities, presentation findings (ptosis, headache, diplopia, extra-ocular movements, Anisocoria, Visual Acuity for both eyes, Media and Fundus examination findings). Contrast Enhanced MRI (CEMRI) results were also tabulated where performed. Potential causes such as diabetes mellitus, hypertension, space occupying lesions, aneurysms and injury were also documented for each patient. Results: A total of 22 patients had 3rd nerve palsy, 9(40.91%) out of them had partial 3rd nerve palsy while 6(27.31%) had ischemic 3rd nerve palsy. Out of 45 cases of 4th and 6th nerve palsy, 13(28.90%) patients had ischemic fourth nerve palsy and 13(28.90%) patients had ischemic 6th nerve palsy, followed by post-traumatic fourth nerve palsy. Conclusion: We have provided an account of the possible etiologies and presentation findings in patients presenting with ocular motility disorders in our setting. Diabetes Mellitus was the most common microvascular cause for ischemic cranial nerve palsies. More sinister pathologies like myasthenia gravis, often presenting as mimickers of isolated cranial nerve palsies were quite common in our study.